2020
DOI: 10.4081/jphia.2020.1138
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with noncompliance of sodium restriction in hypertensive and heart failure patients at the National Hospital of Cotonou, Benin

Abstract: Background: Cancer incidence and mortality is increasing worldwide. In 2018, there were an estimated 18.1 million new cancer cases and 9.6 million cancer deaths. In Nigeria, it is estimated that 100,000 new cases occur annually, with a high case fatality ratio. The burden of cancer in Nigeria is significant, as the country still grapples with infectious diseases and has limited data on cancer epidemiology. Our study is descriptive using data from a hospital-based registry. Objectives: This retrospective study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…There were 16 global studies including the African or SSA regions ( 27 , 46 , 69 , 104 , 106 , 108 , 109 , 117 , 121 , 122 , 127 , 131 , 142 , 144 , 145 , 158 ) and there were 16 African multi-country studies ( 2 , 6 , 87 , 119 , 120 , 138 , 140 , 141 , 143 , 148 154 ). From the single-country studies, majority were done in Nigeria ( n = 17) ( 24 , 25 , 28 , 29 , 34 , 45 , 54 , 64 , 72 , 75 , 92 , 93 , 103 , 113 , 116 , 124 , 137 ) and South Africa ( n = 20) ( 10 , 26 , 36 , 42 , 55 , 65 , 80 83 , 86 , 88 , 89 , 91 , 98 , 105 , 110 , 125 , 129 , 135 ), followed by Uganda ( n = 10) ( 35 , 40 , 48 , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were 16 global studies including the African or SSA regions ( 27 , 46 , 69 , 104 , 106 , 108 , 109 , 117 , 121 , 122 , 127 , 131 , 142 , 144 , 145 , 158 ) and there were 16 African multi-country studies ( 2 , 6 , 87 , 119 , 120 , 138 , 140 , 141 , 143 , 148 154 ). From the single-country studies, majority were done in Nigeria ( n = 17) ( 24 , 25 , 28 , 29 , 34 , 45 , 54 , 64 , 72 , 75 , 92 , 93 , 103 , 113 , 116 , 124 , 137 ) and South Africa ( n = 20) ( 10 , 26 , 36 , 42 , 55 , 65 , 80 83 , 86 , 88 , 89 , 91 , 98 , 105 , 110 , 125 , 129 , 135 ), followed by Uganda ( n = 10) ( 35 , 40 , 48 , …”
Section: Resultsmentioning
confidence: 99%
“…A total of 51 studies reported the prevalence of cervical cancer in Sub-Saharan Africa, of which the majority ( n = 9, 17.6%) were from Nigeria ( 28 , 34 , 45 , 54 , 64 , 92 , 93 , 113 , 137 ); these were retrospective record reviews of registries and patient files and two were cross-sectional studies ( 113 , 137 ). This was followed by six studies from Malawi: one cross-sectional study ( 118 ), one cross-sectional study of the Malawi Cancer Registry ( 133 ), two retrospective cohort studies ( 66 , 68 ) and two retrospective record reviews of registries ( 53 , 67 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nigeria produced 15% of Africa's projected 681,000 new cancer cases in 2008, accounting for around 20% of the continent's population and slightly more than half of West Africa's [2]. In Nigeria, 100,000 new cancer cases are detected each year, with a high case fatality rate [3]. The six most frequent in Nigeria, in descending order of frequency, are breast, cervix, prostate, colorectal, liver, and non-Hodgkins lymphoma [4].…”
Section: Introductionmentioning
confidence: 99%